Disciplinary effect of internal control provisions of SOX on corporate governance structures - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2012)
This study examines whether the internal control provisions under the Sarbanes–Oxley Act (SOX) have a disciplining effect on the governance structures of firms. We find that audit committee members and outside directors of firms that disclose material weaknesses (MWs) under Section 302 of SOX are more likely to leave the firms compared to their counterparts in a matched sample of control firms without such weaknesses, and they lose more outside directorships than their counterparts in the control firms. These results are consistent with the notion that the labor market imposes reputational penalties for internal control failures. Although the MW firms have weaker governance structures than the control firms prior to the MW detection, they show significantly greater improvement in governance structures than the control firms following the detection of these weaknesses. We also find that the market reacts positively to the improvement in audit committee size and board independence, suggesting that the improvement restores investor confidence in financial reporting. Overall, the results in this study show that the internal control provisions of SOX have a disciplining effect on the governance structures of firms.